Method for preparing succinic anhydride based on honeycomb type powder nickel-molybdenum catalyst

By using honeycomb powder nickel-molybdenum catalyst and crystallization separation technology in the process of preparing succinic anhydride in the process of hydrogenation of malaria anhydride, the problems of high reaction pressure and high energy consumption in the existing technology are solved, and high efficiency and low energy consumption preparation of succinic anhydride are achieved.

CN119707889AActive Publication Date: 2025-03-28SHANDONG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510214599.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-28
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

In the prior art, the process of preparing succinic anhydride with a hydrogenation of a manic anhydride has problems of excessive reaction pressure and high energy consumption, which is not conducive to large-scale production and economical production.

Method used

Using a method based on a honeycomb powder nickel-molybdenum catalyst, the honeycomb powder nickel-molybdenum catalyst, malic anhydride, solvent and hydrogen are mixed and then entered into a tubular reactor for hydrogenation, and the succinic anhydride is obtained by crystallization separation, reducing energy consumption.

Benefits of technology

It improves the activity and stability of the catalyst, enhances the efficiency of gas-liquid solid three-phase mass transfer, reduces energy consumption, and realizes efficient preparation of succinic anhydride.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707889A_ABST
    Figure CN119707889A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heterocyclic compounds, and particularly relates to a method for preparing succinic anhydride based on a honeycomb type powder nickel-molybdenum catalyst. The honeycomb type powder nickel molybdenum catalyst, maleic anhydride, a solvent and hydrogen are mixed and then enter a tubular reactor for hydrogenation reaction, and succinic anhydride is obtained through crystal separation. The high activity and high stability of the catalyst are maintained, the gas-liquid-solid three-phase mass transfer efficiency is enhanced, and the energy consumption is greatly reduced by utilizing crystal separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heterocyclic compounds, and specifically relates to a method for preparing succinic anhydride based on a honeycomb-type powdered nickel-molybdenum catalyst. Background Art

[0002] Succinic anhydride is an important fine chemical intermediate, widely used in medicine, agriculture, food and petrochemical industries. Maleic anhydride hydrogenation is a method of preparing succinic anhydride by direct hydrogenation using maleic anhydride as raw material. It has the advantages of simple process flow, convenient operation process, high equipment utilization, low production cost and high product purity. Maleic anhydride hydrogenation method synthesizes succinic anhydride (SAA), γ-butyrolactone (GBL), tetrahydrofuran (THF), 1,4-butanediol (BDO), etc. by selective hydrogenation of C=C bond or C=O bond by gas phase or liquid phase hydrogenation. The use of different catalysts will lead to differences in the products and their distribution of maleic anhydride hydrogenation reaction. Therefore, catalysts and synthesis methods are key factors in the catalytic hydrogenation process.

[0003] There are many reports on the process of preparing succinic anhydride by hydrogenating maleic anhydride in the prior art. U.S. Patent No. 5,952,514A discloses a catalyst pressed with iron, aluminum, silicon, titanium and carbon alloy powder under the conditions of temperature of 60-180° C. and pressure of 38 MPa. A hydrogenation experiment was carried out using a fixed bed to prepare succinic anhydride. Although the yield of succinic anhydride is above 99%, the reaction pressure is too high, which is not conducive to large-scale production.

[0004] Chinese patent CN103570650A discloses a process flow for continuously producing succinic anhydride and succinic acid by hydrogenating maleic anhydride. Maleic anhydride is dissolved in a solvent, and then hydrogenated in a two-stage reactor using a silicon-aluminum heterogeneous catalyst. Finally, the solvent is separated by distillation. The distillation method consumes a lot of energy, which greatly increases the reaction cost.

[0005] At present, the hydrogenation processes of maleic anhydride include intermittent hydrogenation process and continuous hydrogenation process. The intermittent hydrogenation process has disadvantages such as long reaction cycle and unstable product quality; while the continuous hydrogenation process avoids the above problems. However, similar to the intermittent hydrogenation process, the continuous hydrogenation process also has the problem of low gas-liquid-solid three-phase mass transfer efficiency. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing succinic anhydride based on a honeycomb-type powdered nickel-molybdenum catalyst, which maintains the high activity and high stability of the catalyst, enhances the gas-liquid-solid three-phase mass transfer efficiency, and greatly reduces energy consumption by crystallization separation.

[0007] The method for preparing succinic anhydride based on a honeycomb-type powdered nickel-molybdenum catalyst of the present invention is that a honeycomb-type powdered nickel-molybdenum catalyst, maleic anhydride, a solvent and hydrogen are mixed and then introduced into a tubular reactor for hydrogenation reaction, crystallization and separation to obtain succinic anhydride; The preparation method of the honeycomb type powdered nickel-molybdenum catalyst comprises the following steps: (a) nickel nitrate hexahydrate, ammonium molybdate, sodium silicate nonahydrate, urea and PEG6000 are mixed, and then deionized water is added for high-speed shearing to obtain a suspension containing a precipitate; (b) filtering the suspension containing the precipitate to obtain a precipitate; washing the precipitate to neutrality and then adding deionized water to disperse it, spraying and granulating the obtained dispersion to obtain a catalyst precursor; calcining the catalyst precursor, reducing and passivating it in a hydrogen atmosphere to obtain a honeycomb type powdered nickel-molybdenum catalyst.

[0008] In step (a), the mass ratio of nickel nitrate hexahydrate, ammonium molybdate, sodium silicate nonahydrate, urea, PEG6000 and deionized water is 1: 0.016-0.02: 0.5-0.8: 0.8-1.2: 0.02-0.04: 10-30.

[0009] In step (a), the high-speed shearing rate is 800-2000 rpm, the high-speed shearing temperature is 60-120° C., and the high-speed shearing time is 12-36 h.

[0010] In step (b), the mass ratio of precipitate to deionized water is 1:10-12; the pressure of spray granulation is 0.15-0.3MPa, the temperature of spray granulation is 120-180°C; the roasting temperature is 450-650°C, the roasting time is 3-4h; the reduction temperature is 500-700°C, the reduction time is 3-4h; the passivation is carried out at room temperature for 3-4h using N2 containing 0.5-2wt.% O2.

[0011] The mass of the honeycomb type powdered nickel-molybdenum catalyst is 2-6% of the mass of maleic anhydride.

[0012] The solvent is acetic acid, and the mass ratio of the solvent to maleic anhydride is 2-8:1.

[0013] The mass ratio of maleic anhydride to hydrogen is 1:800-1200.

[0014] The hydrogenation reaction temperature is 80-140°C, the hydrogenation reaction pressure is 0.5-3MPa, and the hydrogenation reaction time is 30-180min.

[0015] The crystallization temperature is 20-25°C and the crystallization time is 3-5min.

[0016] The device used in the method for preparing succinic anhydride based on honeycomb-type powder nickel-molybdenum catalyst includes a hydrogen cylinder, which is connected in sequence with a hydrogen cylinder, a premixing kettle, a hydraulic pump, a tubular reactor, a catalyst filter, a crystallization tank, a succinic anhydride filter and a product succinic anhydride storage tank, the premixing kettle is connected to a static mixer, the static mixer is connected to a solvent storage tank, a maleic anhydride storage tank, and a catalyst storage tank, respectively, the solvent storage tank is connected to the succinic anhydride filter, and the catalyst storage tank is connected to the catalyst filter.

[0017] The size range of the honeycomb type powdered nickel-molybdenum catalyst prepared by the invention is 800-1200nm.

[0018] In the present invention, a honeycomb-type powdered nickel-molybdenum catalyst, solvent acetic acid and maleic anhydride are mixed in a static mixer and then enter a premixing kettle to be mixed with hydrogen to obtain a mixed material, and the mixed material is pumped into a tubular reactor by a hydraulic pump, and the gas-liquid-solid three phases are fully mixed in the tubular reactor, and a hydrogenation reaction is performed to obtain maleic anhydride hydrogenation product succinic anhydride. Based on the fact that the solubility of succinic anhydride in acetic acid varies greatly with temperature, the product succinic anhydride is separated by crystallization, and the solvent is recycled.

[0019] The beneficial effects of the present invention are as follows: (1) The honeycomb-type powdered nickel-molybdenum catalyst of the present invention is doped with a second metal, Mo. The introduction of Mo can adjust the d-band center of Ni to make it closer to the Fermi level, thereby optimizing the adsorption capacity of the honeycomb-type powdered nickel-molybdenum catalyst for H and improving the activity of the catalyst. It can also cooperate with Ni to adjust the electronic structure of the catalyst and thus effectively adjust the adsorption behavior of the reactants, thereby improving the selectivity of the catalyst for C=C double bonds.

[0020] (2) The present invention utilizes the synergistic effect of PEG6000, high-speed shearing and spray drying to synthesize a micro-nano particle catalyst with a honeycomb structure. Compared with PEG2000 or PEG8000, the specific molecular weight of PEG6000 (chain length of about 13.6 nm) accurately matches the hydrolysis kinetics of nickel ions: the moderate molecular chain length of PEG6000 can guide the catalyst raw materials to form a stable three-dimensional honeycomb structure through the hydrogen bond network, and will not hinder high-speed shear dispersion due to structural collapse caused by too short chain segments (PEG2000) or too high solution viscosity caused by too long chain segments (PEG8000). The high shear rate field generated by high-speed shearing works synergistically with PEG6000. On the one hand, the local concentration gradient is eliminated through instantaneous uniform mixing, so that the catalyst precursor grows in a directional manner under the guidance of PEG6000. On the other hand, the metal species adsorbed on the surface of the PEG6000 molecular chain are stripped off by shear-induced micro-eddies to avoid the occurrence of active site entrapment. The lower crystallinity of PEG6000 ensures that the metastable honeycomb structure is retained after the shearing action is terminated. The spray drying method can be used to synthesize catalysts with smaller bulk density at a certain temperature and pressure and prevent agglomeration during the drying process.

[0021] (3) The honeycomb structure in the honeycomb powder nickel-molybdenum catalyst has a large specific surface area (450-480m 2 / g), providing a larger contact area for the catalyst, allowing maleic anhydride to diffuse more easily to the surface of the active substance, thereby increasing the speed and efficiency of the catalytic reaction. The passivation method makes the catalyst easier to store in the air.

[0022] (4) During the gas-liquid-solid three-phase transfer process, the micro-nano particle catalyst is better dispersed in the reaction system. The honeycomb structure increases the contact area with hydrogen and maleic anhydride and has higher stability, which promotes hydrogen adsorption and maleic anhydride activation, thereby increasing the hydrogenation reaction rate.

[0023] (5) The present invention uses a crystallization method to separate the products, taking advantage of the solubility characteristics of succinic anhydride in acetic acid. The solubility of succinic anhydride in acetic acid is greatly affected by temperature. At room temperature, more than 95% of succinic anhydride can be crystallized, which greatly reduces the energy consumption of separating the products by distillation.

[0024] (6) The present invention adopts a continuous hydrogenation process, by continuously adding maleic anhydride, acetic acid and a catalyst, so that the C=C double bond concentration of maleic anhydride is balanced during the reaction, thereby ensuring the activity of the catalyst, improving the hydrogenation efficiency, reducing the reaction time and saving energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1The present invention is a schematic structural diagram of the device used in the method for preparing succinic anhydride based on a honeycomb-type powdered nickel-molybdenum catalyst; in the figure: 1, hydrogen cylinder; 2, solvent storage tank; 3, maleic anhydride storage tank; 4, catalyst storage tank; 5, static mixer; 6, premixing kettle; 7, hydraulic pump; 8, tubular reactor; 9, catalyst filter; 10, crystallization tank; 11, succinic anhydride filter; 12, product succinic anhydride storage tank.

[0026] Figure 2 This is the SEM image of the honeycomb-type powdered nickel-molybdenum catalyst prepared in Example 1.

[0027] Figure 3 This is the EDS image of the honeycomb-type powdered nickel-molybdenum catalyst prepared in Example 1.

[0028] Figure 4 This is the particle size distribution diagram of the honeycomb type powdered nickel-molybdenum catalyst prepared in Example 1.

[0029] Figure 5 This is the SEM image of the catalyst prepared in Comparative Example 1.

[0030] Figure 6 This is the SEM image of the catalyst prepared in Comparative Example 2.

[0031] Figure 7 This is the SEM image of the catalyst prepared in Comparative Example 5.

[0032] Figure 8 This is the SEM image of the catalyst prepared in Comparative Example 6. DETAILED DESCRIPTION

[0033] The present invention is further described below with reference to the embodiments.

[0034] Example 1 like Figure 1 As shown, the device used in the method for preparing succinic anhydride based on honeycomb type powder nickel-molybdenum catalyst includes a hydrogen cylinder 1, the hydrogen cylinder 1, the premixing kettle 6, the hydraulic pump 7, the tubular reactor 8, the catalyst filter 9, the crystallization tank 10, the succinic anhydride filter 11 and the product succinic anhydride storage tank 12 are connected in sequence, the premixing kettle 6 is connected to the static mixer 5, the static mixer 5 is respectively connected to the solvent storage tank 2, the maleic anhydride storage tank 3, and the catalyst storage tank 4, the solvent storage tank 2 is connected to the succinic anhydride filter 11, and the catalyst storage tank 4 is connected to the catalyst filter 9.

[0035] The preparation method of honeycomb type powdered nickel-molybdenum catalyst comprises the following steps: (a) 10 g of nickel nitrate hexahydrate, 0.184 g of ammonium molybdate, 6 g of sodium silicate nonahydrate, 10 g of urea and 0.2 g of PEG6000 were mixed, 300 g of deionized water was added, and high-speed shearing was performed at 90° C. and 1200 rpm for 20 h to obtain a suspension containing a precipitate; (b) filtering the suspension containing the precipitate to obtain a precipitate; washing the precipitate to neutrality and then adding deionized water to disperse it, the mass ratio of the precipitate to deionized water being 1:10, spray granulating the obtained dispersion to obtain a catalyst precursor, the pressure of the spray granulation being 0.3 MPa, and the temperature of the spray granulation being 120°C; calcining the catalyst precursor at 600°C for 4 h, reducing it at 600°C in a hydrogen atmosphere for 4 h, and passivating it with N2 containing 1 wt.% O2 at room temperature for 3.5 h to obtain a honeycomb type powdered nickel-molybdenum catalyst.

[0036] The SEM image of the honeycomb powder nickel-molybdenum catalyst is shown in Figure 2 The EDS analysis results of honeycomb type powdered nickel-molybdenum catalyst are shown in Figure 3 And Table 1. The particle size distribution of honeycomb type powdered nickel-molybdenum catalyst is shown in Figure 4 The average size of the honeycomb powder nickel-molybdenum catalyst is 1000nm, and its specific surface area is 469.4m 2 / g.

[0037]

[0038] The method for preparing succinic anhydride based on honeycomb type powder nickel-molybdenum catalyst comprises the following steps: Before the hydrogenation reaction, the entire device is purged with nitrogen to ensure that the nitrogen fills the device; 0.04g / min of honeycomb powder nickel-molybdenum catalyst, 8g / min of acetic acid and 1g / min of maleic anhydride enter the static mixer 5 for mixing, and then enter the premixing kettle 6 to mix with 1000g / min of hydrogen. The obtained mixed material enters the tubular reactor 8 through the hydraulic pump 7 for hydrogenation reaction. The hydrogenation reaction temperature is 80°C, the hydrogenation reaction pressure is 1MPa, and the hydrogenation reaction time is 60min. The obtained reaction material is filtered out of the catalyst through the catalyst filter 9 to obtain a liquid material. The liquid material enters the crystallization tank 10 and crystallizes at 20°C for 5min. The obtained crystallized material enters the succinic anhydride filter 11 for filtration. The obtained succinic anhydride enters the product succinic anhydride storage tank 12, and the remaining liquid (containing a small amount of maleic anhydride and succinic anhydride) returns to the solvent storage tank 2 for recycling.

[0039] The liquid material obtained after filtering out the catalyst through the catalyst filter 9 was subjected to gas chromatography test. Chromatographic conditions: Agilent HP-5 chromatographic column, injection port temperature 240°C, FID detector temperature 240°C, column flow rate 1ml / min, hydrogen flow rate 30ml / min, air flow rate 400ml / min, program heating mode: 80°C for 2min, then heated to 220°C at 15°C / min, and maintained for 15min. The gas chromatography test results of 6 cycles are shown in Table 2. As can be seen from Table 2, after 6 cycles, the maleic anhydride conversion rate and succinic anhydride selectivity are maintained at a high level, indicating that the stability of the honeycomb powder nickel-molybdenum catalyst is good.

[0040]

[0041] Example 2 The apparatus used in the method for preparing succinic anhydride based on honeycomb-type powdered nickel-molybdenum catalyst is the same as that in Example 1.

[0042] The preparation method of honeycomb type powdered nickel-molybdenum catalyst comprises the following steps: (a) 10 g of nickel nitrate hexahydrate, 0.16 g of ammonium molybdate, 5 g of sodium silicate nonahydrate, 12 g of urea and 0.3 g of PEG6000 were mixed, 100 g of deionized water was added, and high-speed shearing was performed at 60° C. and 800 rpm for 36 h to obtain a suspension containing a precipitate; (b) filtering the suspension containing the precipitate to obtain the precipitate; washing the precipitate to neutrality, adding deionized water to disperse it, the mass ratio of the precipitate to the deionized water being 1:11, spray granulating the obtained dispersion to obtain a catalyst precursor, the pressure of the spray granulation being 0.2 MPa, and the temperature of the spray granulation being 150°C; calcining the catalyst precursor at 450°C for 3 h, reducing it at 500°C for 3 h in a hydrogen atmosphere, and passivating it with N2 containing 0.5 wt.% O2 at room temperature for 3 h to obtain a honeycomb type powdered nickel-molybdenum catalyst.

[0043] The method for preparing succinic anhydride based on honeycomb type powder nickel-molybdenum catalyst comprises the following steps: Before the hydrogenation reaction, the entire device is purged with nitrogen to ensure that the nitrogen fills the device; 0.06 g / min of honeycomb powder nickel-molybdenum catalyst, 6 g / min of acetic acid and 1 g / min of maleic anhydride enter the static mixer 5 for mixing, and then enter the premixing kettle 6 to mix with 1200 g / min of hydrogen. The obtained mixed material enters the tubular reactor 8 through the hydraulic pump 7 for hydrogenation reaction. The hydrogenation reaction temperature is 140°C, the hydrogenation reaction pressure is 0.5 MPa, and the hydrogenation reaction time is 30 min. The obtained reaction material is filtered out of the catalyst through the catalyst filter 9 to obtain a liquid material. The liquid material enters the crystallization tank 10 and crystallizes at 25°C for 3 min. The obtained crystallized material enters the succinic anhydride filter 11 for filtration. The obtained succinic anhydride enters the product succinic anhydride storage tank 12, and the remaining liquid (containing a small amount of maleic anhydride and succinic anhydride) returns to the solvent storage tank 2 for recycling.

[0044] The liquid material obtained after filtering out the catalyst through the catalyst filter 9 was subjected to gas chromatography test. Chromatographic conditions: Agilent HP-5 chromatographic column, injection port temperature 240°C, FID detector temperature 240°C, column flow rate 1ml / min, hydrogen flow rate 30ml / min, air flow rate 400ml / min, program temperature rise mode: 80°C for 2min, then heated to 220°C at 15°C / min, and held for 15min. The gas chromatography test results of 6 cycles of reaction are shown in Table 3.

[0045]

[0046] Example 3 The apparatus used in the method for preparing succinic anhydride based on honeycomb-type powdered nickel-molybdenum catalyst is the same as that in Example 1.

[0047] The preparation method of honeycomb type powdered nickel-molybdenum catalyst comprises the following steps: (a) 10 g of nickel nitrate hexahydrate, 0.2 g of ammonium molybdate, 8 g of sodium silicate nonahydrate, 8 g of urea and 0.4 g of PEG6000 were mixed, 200 g of deionized water was added, and high-speed shearing was performed at 120° C. and 2000 rpm for 12 h to obtain a suspension containing a precipitate; (b) filtering the suspension containing the precipitate to obtain a precipitate; washing the precipitate to neutrality, adding deionized water to disperse it, the mass ratio of the precipitate to deionized water being 1:12, spray granulating the obtained dispersion to obtain a catalyst precursor, the pressure of the spray granulation being 0.15 MPa, and the temperature of the spray granulation being 180°C; calcining the catalyst precursor at 650°C for 3.5 h, reducing it at 700°C for 3.5 h in a hydrogen atmosphere, and passivating it with N2 containing 2 wt.% O2 at room temperature for 4 h to obtain a honeycomb type powdered nickel-molybdenum catalyst.

[0048] The method for preparing succinic anhydride based on honeycomb type powder nickel-molybdenum catalyst comprises the following steps: Before the hydrogenation reaction, the entire device is purged with nitrogen to ensure that the device is filled with nitrogen; 0.02g / min of honeycomb powder nickel-molybdenum catalyst, 2g / min of acetic acid and 1g / min of maleic anhydride enter the static mixer 5 for mixing, and then enter the premixing kettle 6 to mix with 800g / min of hydrogen, and the obtained mixed material enters the tubular reactor 8 through the hydraulic pump 7 for hydrogenation reaction. The hydrogenation reaction temperature is 120°C, the hydrogenation reaction pressure is 3MPa, and the hydrogenation reaction time is 180min. The obtained reaction material is filtered out of the catalyst through the catalyst filter 9 to obtain a liquid material, and the liquid material enters the crystallization tank 10 to crystallize at 23°C for 4min, and the obtained crystal material enters the succinic anhydride filter 11 for filtration, and the obtained succinic anhydride enters the product succinic anhydride storage tank 12, and the remaining liquid (containing a small amount of maleic anhydride and succinic anhydride) returns to the solvent storage tank 2 for recycling.

[0049] The liquid material obtained after filtering out the catalyst through the catalyst filter 9 was subjected to gas chromatography test. Chromatographic conditions: Agilent HP-5 chromatographic column, injection port temperature 240°C, FID detector temperature 240°C, column flow rate 1ml / min, hydrogen flow rate 30ml / min, air flow rate 400ml / min, program temperature rise mode: 80°C for 2min, then heated to 220°C at 15°C / min, and held for 15min. The gas chromatography test results of 6 cycles of reaction are shown in Table 4.

[0050]

[0051] Comparative Example 1 In step (a), high-speed shearing was not performed, and the other steps were the same as in Example 1. The SEM image of the obtained catalyst is shown in Figure 5 ,Depend on Figure 5 It can be seen that the obtained catalyst is not a honeycomb structure, and its specific surface area is measured to be 311.7 m 2 / g. The gas chromatography test results of 6 cycles of reaction are shown in Table 5. As shown in Table 5, compared with Example 1, the maleic anhydride conversion rate of Comparative Example 1 decreases rapidly with the increase of the number of cycles of reaction, indicating that the catalyst stability of Comparative Example 1 is poor, and the selectivity of succinic anhydride of Comparative Example 1 is lower than that of Example 1.

[0052]

[0053] Comparative Example 2 In step (a), PEG6000 was not added, and the other steps were the same as in Example 1. The SEM image of the obtained catalyst is shown in Figure 6 ,Depend on Figure 6It can be seen that the obtained catalyst is not a honeycomb structure, and its specific surface area is measured to be 218.0 m 2 / g. The gas chromatography test results of 6 cycles of reaction are shown in Table 6. As shown in Table 6, compared with Example 1, the maleic anhydride conversion rate of Comparative Example 2 decreases rapidly with the increase of the number of cycles, and the selectivity of succinic anhydride in Comparative Example 2 is lower than that in Example 1, which indicates that the catalyst in Comparative Example 2 is not stable enough and has poor selectivity.

[0054]

[0055] Comparative Example 3 Ammonium molybdate was not added in step (a), and the other steps were the same as in Example 1. The gas chromatography test results of the 6-cycle reaction are shown in Table 7. As can be seen from Table 7, compared with Example 1, the selectivity of succinic anhydride in Comparative Example 3 is lower than that in Example 1, indicating that the catalyst selectivity of Comparative Example 3 is poor.

[0056]

[0057] Comparative Example 4 In step (b), spray granulation was not performed, and the other steps were the same as in Example 1. The gas chromatography test results of 6 cycles of reaction are shown in Table 8. As shown in Table 8, compared with Example 1, the maleic anhydride conversion rate of Comparative Example 4 decreases rapidly with the increase of the number of cycles of reaction, indicating that the catalyst stability of Comparative Example 4 is poor.

[0058]

[0059] Comparative Example 5 In step (a), PEG6000 was replaced by PEG2000, and the other steps were the same as in Example 1. The SEM image of the obtained catalyst is shown in Figure 7 ,Depend on Figure 7 It can be seen that the obtained catalyst is not a honeycomb structure, and its specific surface area is measured to be 283.8m 2 / g. The gas chromatography test results of 6 cycles of reaction are shown in Table 9. As shown in Table 9, compared with Example 1, the maleic anhydride conversion rate of Comparative Example 5 decreases rapidly with the increase of the number of cycles of reaction, indicating that the catalyst stability of Comparative Example 5 is poor; and the selectivity of succinic anhydride in Comparative Example 5 is lower than that in Example 1.

[0060]

[0061] Comparative Example 6 In step (a), PEG6000 was replaced by PEG8000, and the other steps were the same as in Example 1. The SEM image of the obtained catalyst is shown in Figure 8 ,Depend on Figure 8It can be seen that the obtained catalyst is not a honeycomb structure, and its specific surface area is measured to be 323.4m 2 / g. The gas chromatography test results of 6 cycles of reaction are shown in Table 10. As shown in Table 10, compared with Example 1, the maleic anhydride conversion rate of Comparative Example 6 decreases rapidly with the increase of the number of cycles of reaction, indicating that the catalyst stability of Comparative Example 6 is poor; and the selectivity of succinic anhydride in Comparative Example 6 is lower than that in Example 1.

[0062]

Claims

1. A method for preparing succinic anhydride based on a honeycomb-type powdered nickel-molybdenum catalyst, characterized in that A honeycomb-type powdered nickel-molybdenum catalyst, maleic anhydride, solvent and hydrogen are mixed and then introduced into a tubular reactor (8) for hydrogenation reaction, followed by crystallization and separation to obtain succinic anhydride; The preparation method of the honeycomb type powdered nickel-molybdenum catalyst comprises the following steps: (a) nickel nitrate hexahydrate, ammonium molybdate, sodium silicate nonahydrate, urea and PEG6000 are mixed, and then deionized water is added for high-speed shearing to obtain a suspension containing a precipitate; (b) filtering the suspension containing the precipitate to obtain a precipitate; washing the precipitate to neutrality and then adding deionized water to disperse it, spraying and granulating the obtained dispersion to obtain a catalyst precursor; calcining the catalyst precursor, reducing and passivating it in a hydrogen atmosphere to obtain a honeycomb type powdered nickel-molybdenum catalyst.

2. The method for preparing succinic anhydride based on a honeycomb-type powder nickel-molybdenum catalyst according to claim 1, characterized in that In step (a), the mass ratio of nickel nitrate hexahydrate, ammonium molybdate, sodium silicate nonahydrate, urea, PEG6000 and deionized water is 1: 0.016-0.02: 0.5-0.8: 0.8-1.2: 0.02-0.04: 10-30.

3. The method for preparing succinic anhydride based on a honeycomb-type powdered nickel-molybdenum catalyst according to claim 1, characterized in that In step (a), the high-speed shearing rate is 800-2000 rpm, the high-speed shearing temperature is 60-120° C., and the high-speed shearing time is 12-36 h.

4. The method for preparing succinic anhydride based on honeycomb-type powdered nickel-molybdenum catalyst according to claim 1, characterized in that In step (b), the mass ratio of precipitate to deionized water is 1:10-12; the pressure of spray granulation is 0.15-0.3MPa, the temperature of spray granulation is 120-180°C; the roasting temperature is 450-650°C, the roasting time is 3-4h; the reduction temperature is 500-700°C, the reduction time is 3-4h; the passivation is carried out at room temperature for 3-4h using N2 containing 0.5-2wt.% O2.

5. The method for preparing succinic anhydride based on honeycomb-type powdered nickel-molybdenum catalyst according to claim 1, characterized in that The mass of the honeycomb type powdered nickel-molybdenum catalyst is 2-6% of the mass of maleic anhydride.

6. The method for preparing succinic anhydride based on honeycomb-type powdered nickel-molybdenum catalyst according to claim 1, characterized in that The solvent is acetic acid, and the mass ratio of the solvent to maleic anhydride is 2-8:

1.

7. The method for preparing succinic anhydride based on honeycomb-type powdered nickel-molybdenum catalyst according to claim 1, characterized in that The mass ratio of maleic anhydride to hydrogen is 1:800-1200.

8. The method for preparing succinic anhydride based on honeycomb-type powdered nickel-molybdenum catalyst according to claim 1, characterized in that The hydrogenation reaction temperature is 80-140°C, the hydrogenation reaction pressure is 0.5-3MPa, and the hydrogenation reaction time is 30-180min.

9. The method for preparing succinic anhydride based on honeycomb type powder nickel-molybdenum catalyst according to claim 1, characterized in that The crystallization temperature is 20-25°C and the crystallization time is 3-5min.

10. The method for preparing succinic anhydride based on honeycomb-type powdered nickel-molybdenum catalyst according to claim 1, characterized in that The device used in the method for preparing succinic anhydride based on honeycomb-type powdered nickel-molybdenum catalyst comprises a hydrogen cylinder (1), wherein the hydrogen cylinder (1), a premixing kettle (6), a hydraulic pump (7), a tubular reactor (8), a catalyst filter (9), a crystallization tank (10), a succinic anhydride filter (11) and a product succinic anhydride storage tank (12) are connected in sequence, the premixing kettle (6) is connected to a static mixer (5), the static mixer (5) is respectively connected to a solvent storage tank (2), a maleic anhydride storage tank (3) and a catalyst storage tank (4), the solvent storage tank (2) is connected to the succinic anhydride filter (11), and the catalyst storage tank (4) is connected to the catalyst filter (9).

Citation Information

Patent Citations

  • Technological process for continuously producing succinic anhydride and co-producing succinic acid through maleic anhydride hydrogenation

    CN103570650A

  • Process for preparing succinic anhydride

    US5952514A

  • Method for generating succinic anhydride through maleic anhydride hydrogenation catalyzed by Nano-Ni

    CN102229587A

  • Catalyst for hydrogenating cis-butenedioic anhydride to prepare butanedioic anhydride and its preparation method and application

    CN103769117A

  • Recyclable Ru nano catalyst, preparation method thereof and application thereof in preparation of cis-pinane

    CN111545195A